Homomorphisms similar to completely contractive homomorphims - Pacheco, Wilson (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
Paulsen has proved that a unital homomorphism from an operator algebra contained in a C* - algebra is similar to a completely contractive homomorphism if and only if it is completely bounded. In the present note we obtain a different characterization when the operator algebra is separable.